Genetic causal relationship between age at menarche and benign oesophageal neoplasia identified by a Mendelian randomization study - Su, Yani; Hu, Yunfeng; Xu, Yiwei; Yang, Mingyi; Wu, Fangcai; Peng, Yuhui (Frontiers in Endocrinology, 2023)
Objective: Oesophagus Neoplasm (ON) is a kind of disease related to hormone changes, and hormone level is closely related to the occurrence and development of the disease. The aim of this study was to investigate the causal relationship between age at menarche (AAMA) and age at menopause (AAMO) and Benign Oesophagus neoplasm (BON) and Malignant Oesophagus neoplasm (MON) from a genetic perspective. Methods: Genome-wide association study (GWAS) summary data of exposure (AAMA and AAMO) and outcome (BON and MON) were obtained from the IEU Open GWAS database. We performed a two-sample Mendelian randomization (MR) study between them through the TwoSampleMR and MRPRESSO packages of the R software. The inverse variance weighted (IVW) as the main analysis method, the MR Egger, Weighted median, Simple mode, and Weighted mode as the supplementary methods, and the Maximum likelihood, Penalised weighted median, and IVW (fixed effects) as the validation methods. Results: The random-effects IVW results showed that AAMA had negative genetic causal relationship with BON (P = 0.002, OR 95% confidence interval [CI] = 0.285 [0.130-0.623]). The Weighted median, Maximum likelihood, Penalised weighted median, and IVW (fixed effects) were consistent with random-effects IVW (P < 0.05). The MR Egger, Simple mode and Weighted mode results showed that AAMA had no genetic causal relationship with BON (P > 0.05). The random-effects IVW results showed that there had no genetic causal relationship between AAMO and BON (P = 0.935, OR 95% CI = 0.989 [0.755-1.296]), between AAMA and MON (P = 0.685, OR 95% CI = 1.132 [0.621-2.063]), between AAMO and MON (P = 0.200, OR 95% CI = 1.129 [0.938-1.359]), respectively. The MR Egger, Weighted median, Simple mode, Weighted mode Maximum likelihood, Penalised weighted median, and IVW (fixed effects) were consistent with random-effects IVW (P < 0.05). Our MR analysis had no heterogeneity, horizontal pleiotropy and outliers. Conclusion: Our study showed that AAMA had negative genetic causal relationship with BON, and there was no genetic causal relationship between AAMA and MON, and between AAMO and BON and MON. But it could not be ruled out that they were related at other levels besides genetics.